The Australian and New Zealand Clinician Educator Network (ANZCEN) Unconference: What's an unconference and how can it develop communities of practice?. Issue 2 (4th March 2021) - Ross, Paul; Moon, Kylie; Paras, Annie; Long, Paul; Paterson, Sheree; Ghani, Manisa; Knott, Cameron; Lister, Bruce; Nickson, Christopher; Massey, Debbie
ABSTRACT: The Australian and New Zealand Clinician Educator Network (ANZCEN) is a collaborative interprofessional group developed to promote the development of education in critical care healthcare practice. In November 2018, 45 critical care practitioners met at the first ANZCEN Unconference. In an unconference, the participants drive the agenda, and learning occurs from the active process of engaging in a community of practice. The aim of this unconference was to develop an innovative approach to learning through a collaborative framework with interprofessional representation across critical care specialties. Four key themes were identified in the unconference as drivers of interprofessional critical care educational priorities: interprofessional learning, workplace learning, faculty development, research, and scholarship. In this discussion paper, we describe our experiences organizing, participating in, and evaluating an unconference, and we examine its usefulness as a medium for promoting the interprofessional learning agenda in critical care. We hope that the processes outlined in this discussion paper will provide a useful resource for other clinicians who are considering developing an unconference. Finally, we argue that the unconference offers a unique and important model for future education of critical care practitioners where the emphasis on collaboration and communication through interprofessional learning and practice will be required to improve health outcomes and promote a patient-centered model of care.